GAME DEVELOPMENT “GEMAS (MODIFIED DIVISION ENGKLEK GAME)” TO IMPROVE UNDERSTANDING OF CONCEPTSIN CLASS II ELEMENTARY SCHOOL STUDENTS - Annisa Amaliyatus Sofiyati; Ahmad Arifuddin; Wulan Andini (Al-Mudarris: Journal Of Education, 2024)
This research aims to develop a game "GEMAS (Modified Division Engklek Game)” to improve understanding of concepts for class II elementary school students that meet the criteria of valid, practical and effective. This research uses R&D research with the ASSURE development model. Participants in this research were 16 students. Data collected through questionnaires and tests. The collected data was analyzed through descriptive statistics, paired sample t-test and n-gain test. Based on the research results, it shows that the game GEMAS very worthy to use, where the average score from the validation results of media experts is 99% and material experts 77% . The results of the analysis are related to the practicality of the game GEMAS very practical, where the teacher response was 99% and student response was 99,4%. Based on the test scores for understanding the concept of division, the average results were obtained pretest 62 and posttest 85,44 there was an increase of 0,64 in the medium category. As well as the results of the paired sample t-test, the Sig value was obtained. (2-tailed) of 0,000 < 0,05. So, it can be concluded that game media GEMAS can be declared effective in increasing students' understanding of the concept of division.